How are the articles in compilation of Islamic law contrary to sharia in the books of fiqh? A Book Review Ahli Waris Pengganti, Pasal Waris Bermasalah dalam Kompilasi Hukum Islam (KHI), Ahmad Zarkasih, Rumah Fiqih Publishing, 79 Pages, ISBN XXX-XXXXXX-XXX - Banjaransari, Ayu Putri Rainah Petung (Indonesian Journal of Advocacy and Legal Services, 2020)
It is a book review of a book entitled Ã¢â‚¬Å“Ahli Waris Pengganti, Pasal Waris Bermasalah dalam Kompilasi Hukum IslamÃ¢â‚¬Â that is written by Ahmad Zarkasih, Lc. It consists of 5 chapters and contains problematic inheritance articles in. It is published by Rumah Fiqih Publishing, which is located in Kuningan, South Jakarta. This book is the first print that was printed on August 22, 2019 yesterday. The purpose of the author regarding this writing is to give information about articles of troubled inheritance. As the main discussion, this writing discusses Article 185 in Compilation of Inheritance Law that contains materials of substitute heirs. It explains Article 173 and Article 194 (1) as a complement in examining that Article. It also gives argumens and criticals of thought of experts, especially Prof. Hazairin who triggered Article of troubled inheritance regarding this book entitled Ã¢â‚¬Å“Hukum Waris Bilateral Menurut al-QurÃ¢â‚¬â„¢anÃ¢â‚¬Â.